The Gozitan dialect of Xewkija: three recorded dialogues and some preliminary remarks - Klimiuk, Maciej; Lipnicka, Maria ("Telling of olden kings", 2023)
Abstract Xewkija is the fourth largest locality on the island of Gozo in the Malta archipelago, whose dialects are classified as Maltese rural dialects. The characteristic feature of these is the occurrence of the vowel shift *ā to o. The article presents three dialogues in the dialect of Xewkija in transcription, English translation and standard Maltese. The dialogues are followed by a discussion on select issues such as consonants, vowels, diphthongs, pausal forms, ʔimāla, tafxīm (ʔišmām) and sandhi.